Quercus ilex recruitment in a drier world: A multi-stage demographic approach - Pérez-Ramos, Ignacio M.; Rodriguez-Calcerrada, Jesus; Ourcival, Jean M.; Rambal, Serge (Perspectives in Plant Ecology, Evolution and Systematics, 2013)
There is a growing interest in understanding and forecasting the responses of plant communities to projected changes of environmental conditions. Multi-stage demographic approaches, where plant recruitment is explored across multiple and consecutive stages, are essential to obtain a whole overview of the consequences of increasing aridity on tree recruitment and forest dynamics, but they are still rarely used. In this study, we present the results of an experimental rainfall exclusion aimed to evaluate the impact of projected increasing drought on multiple stage-specific probabilities of recruitment in a key tree species typical of late-successional Mediterranean woodlands (Quercus ilex L.). We calibrated linear and nonlinear likelihood models for the different demographic processes and calculated overall probabilities of recruitment along a wide range of microhabitat conditions. Rainfall exclusion altered Q. ilex recruitment throughout ontogeny. Seed maturation, seedling emergence and survival and, to a lesser extent, post-dispersal seed survival were the most sensitive demographic processes to decreased rainfall. Interestingly, both the identity of the most critical stages for recruitment and their specific sensitivity to rainfall manipulation depended largely on the yearly pattern of precipitation. The microhabitat heterogeneity strongly determined the success of recruitment in the study species. The experimental increase in drought displaced the peak of maximum overall recruitment towards the low end of the light gradient, suggesting that the dependence on shrubs for an effective recruitment in Q. ilex could be intensified under future environmental scenarios. In terms of phenotypic plasticity, Q. ilex seedlings responded more strongly to light availability than to experimentally increased drought, which could reduce its ability to persist under on-going environmental conditions due to climate change. Results from this study provide a full picture of the ecological and functional consequences of the projected rainfall reduction on tree recruitment and forest dynamics in two years of contrasting precipitation.
The following values have no corresponding Zotero field: publisher: Elsevier GmbH.
Keywords: climate change; functional traits; Mediterranean woodland; Microhabitats; regeneration niche; seedling growth

Quercus ilex recruitment in a drier world: A multi-stage demographic approach - Pérez-Ramos, Ignacio M; Rodriguez-Calcerrada, Jesus; Ourcival, Jean M; Rambal, Serge (Perspectives in Plant Ecology, Evolution and Systematics, 2013)
There is a growing interest in understanding and forecasting the responses of plant communities to projected changes of environmental conditions. Multi-stage demographic approaches, where plant recruitment is explored across multiple and consecutive stages, are essential to obtain a whole overview of the consequences of increasing aridity on tree recruitment and forest dynamics, but they are still rarely used. In this study, we present the results of an experimental rainfall exclusion aimed to evaluate the impact of projected increasing drought on multiple stage-specific probabilities of recruitment in a key tree species typical of late-successional Mediterranean woodlands (Quercus ilex L.). We calibrated linear and nonlinear likelihood models for the different demographic processes and calculated overall probabilities of recruitment along a wide range of microhabitat conditions. Rainfall exclusion altered Q. ilex recruitment throughout ontogeny. Seed maturation, seedling emergence and survival and, to a lesser extent, post-dispersal seed survival were the most sensitive demographic processes to decreased rainfall. Interestingly, both the identity of the most critical stages for recruitment and their specific sensitivity to rainfall manipulation depended largely on the yearly pattern of precipitation. The microhabitat heterogeneity strongly determined the success of recruitment in the study species. The experimental increase in drought displaced the peak of maximum overall recruitment towards the low end of the light gradient, suggesting that the dependence on shrubs for an effective recruitment in Q. ilex could be intensified under future environmental scenarios. In terms of phenotypic plasticity, Q. ilex seedlings responded more strongly to light availability than to experimentally increased drought, which could reduce its ability to persist under on-going environmental conditions due to climate change. Results from this study provide a full picture of the ecological and functional consequences of the projected rainfall reduction on tree recruitment and forest dynamics in two years of contrasting precipitation.
Keywords: climate change; functional traits; Mediterranean woodland; Microhabitats; regeneration niche; seedling growth

The temporal response to drought in a Mediterranean evergreen tree: comparing a regional precipitation gradient and a throughfall exclusion experiment - Martin-StPaul, Nicolas K.; Limousin, Jean-Marc; Vogt-Schilb, Helene; Rodriguez-Calcerrada, Jesus; Rambal, Serge; Longepierre, Damien; Misson, Laurent (GLOBAL CHANGE BIOLOGY, 2013)
Like many midlatitude ecosystems, Mediterranean forests will suffer longer and more intense droughts with the ongoing climate change. The responses to drought in long-lived trees differ depending on the time scale considered, and short-term responses are currently better understood than longer term acclimation. We assessed the temporal changes in trees facing a chronic reduction in water availability by comparing leaf-scale physiological traits, branch-scale hydraulic traits, and stand-scale biomass partitioning in the evergreen Quercus ilex across a regional precipitation gradient (long-term changes) and in a partial throughfall exclusion experiment (TEE, medium term changes). At the leaf scale, gas exchange, mass per unit area and nitrogen concentration showed homeostatic responses to drought as they did not change among the sites of the precipitation gradient or in the experimental treatments of the TEE. A similar homeostatic response was observed for the xylem vulnerability to cavitation at the branch scale. In contrast, the ratio of leaf area over sapwood area (LA/SA) in young branches exhibited a transient response to drought because it decreased in response to the TEE the first 4years of treatment, but did not change among the sites of the gradient. At the stand scale, leaf area index (LAI) decreased, and the ratios of stem SA to LAI and of fine root area to LAI both increased in trees subjected to throughfall exclusion and from the wettest to the driest site of the gradient. Taken together, these results suggest that acclimation to chronic drought in long-lived Q. ilex is mediated by changes in hydraulic allometry that shift progressively from low (branch) to high (stand) organizational levels, and act to maintain the leaf water potential within the range of xylem hydraulic function and leaf photosynthetic assimilation.
The following values have no corresponding Zotero field: pub-location: 111 RIVER ST, HOBOKEN 07030-5774, NJ USA publisher: WILEY-BLACKWELL
Keywords: allometry; carbon allocation; chronic stress; ecosystem manipulation; hydraulic adjustments; leaf ecophysiology; long-term drought; Quercus ilex; Water availability

The temporal response to drought in a Mediterranean evergreen tree: comparing a regional precipitation gradient and a throughfall exclusion experiment - Martin-StPaul, Nicolas K; Limousin, Jean-Marc; Vogt-Schilb, Helene; Rodriguez-Calcerrada, Jesus; Rambal, Serge; Longepierre, Damien; Misson, Laurent (GLOBAL CHANGE BIOLOGY, 2013)
Like many midlatitude ecosystems, Mediterranean forests will suffer longer and more intense droughts with the ongoing climate change. The responses to drought in long-lived trees differ depending on the time scale considered, and short-term responses are currently better understood than longer term acclimation. We assessed the temporal changes in trees facing a chronic reduction in water availability by comparing leaf-scale physiological traits, branch-scale hydraulic traits, and stand-scale biomass partitioning in the evergreen Quercus ilex across a regional precipitation gradient (long-term changes) and in a partial throughfall exclusion experiment (TEE, medium term changes). At the leaf scale, gas exchange, mass per unit area and nitrogen concentration showed homeostatic responses to drought as they did not change among the sites of the precipitation gradient or in the experimental treatments of the TEE. A similar homeostatic response was observed for the xylem vulnerability to cavitation at the branch scale. In contrast, the ratio of leaf area over sapwood area (LA/SA) in young branches exhibited a transient response to drought because it decreased in response to the TEE the first 4years of treatment, but did not change among the sites of the gradient. At the stand scale, leaf area index (LAI) decreased, and the ratios of stem SA to LAI and of fine root area to LAI both increased in trees subjected to throughfall exclusion and from the wettest to the driest site of the gradient. Taken together, these results suggest that acclimation to chronic drought in long-lived Q. ilex is mediated by changes in hydraulic allometry that shift progressively from low (branch) to high (stand) organizational levels, and act to maintain the leaf water potential within the range of xylem hydraulic function and leaf photosynthetic assimilation.
Keywords: allometry; carbon allocation; chronic stress; ecosystem manipulation; hydraulic adjustments; leaf ecophysiology; long-term drought; Quercus ilex; Water availability

Gas exchange and leaf aging in an evergreen oak: causes and consequences for leaf carbon balance and canopy respiration - Rodriguez-Calcerrada, Jesus; Limousin, Jean-Marc; Martin-StPaul, Nicolas K; Jaeger, Carsten; Rambal, Serge (Tree Physiology, 2012)
Leaves of Mediterranean evergreens experience large variations in gas exchange rates over their life span due to aging and seasonally changing environmental conditions. Accounting for the changing respiratory physiology of leaves over time will help improve estimations of leaf and whole-plant carbon balances. Here we examined seasonal variations in light-saturated net CO2 assimilation (Amax), dark respiration (Rd) and the proportional change in Rd per 10 °C change in temperature (Q10 of Rd) in previous-year (PY) and current-year (CY) leaves of the broadleaved evergreen tree Quercus ilex L. Amax and Rd were lower in PY than in CY leaves. Differences in nitrogen between cohorts only partly explained such differences, and rates of Amax and Rd expressed per unit of leaf nitrogen were still significantly different between cohorts. The decline in Amax in PY leaves did not result in the depletion of total non-structural carbohydrates, whose concentration was in fact higher in PY than CY leaves. Leaf-level carbon balance modeled from gas exchange data was positive at all ages. Q10 of Rd did not differ significantly between leaf cohorts; however, failure to account for distinct Rd between cohorts misestimated canopy leaf respiration by 13% across dates when scaling up leaf measurements to the canopy. In conclusion, the decline in Amax in old leaves that are close to or exceed their mean life span does not limit the availability of carbohydrates, which are probably needed to sustain new growth, as well as Rd and nutrient resorption during senescence. Accounting for leaf age as a source of variation of Rd improves the estimation of foliar respiratory carbon release at the stand scale.
10.1093/treephys/tps020
Keywords: carbon budget; ecosystem respiration; leaf life span; resource remobilization; soluble sugars; temperature sensitivity

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M.; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
The following values have no corresponding Zotero field: accession-num: 22159896
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Leaf CO2 efflux is attenuated by acclimation of respiration to heat and drought in a Mediterranean tree - Rodriguez-Calcerrada, Jesus; Jaeger, Carsten; Limousin, Jean M; Ourcival, Jean M; Joffre, Richard; Rambal, Serge (Functional Ecology, 2011)
* 1Understanding the effect of water deficit on plant respiration and its temperature sensitivity at long time-scales is important for anticipating the shift in ecosystem dynamics that is expected to occur as a result of climate change. * 2We investigated seasonal variations of leaf dark respiration and sensitivity to temperature in the upper and lower canopy of Quercus ilex trees in a forest stand that had been exposed to either 33% throughfall reduction or normal rainfall for the preceding 6 years. * 3For upper and lower canopy leaves, light-saturated photosynthesis and respiration at a reference temperature of 15 °C (R15) had the lowest values in late summer, when both traits were lower in trees subjected to throughfall reduction than in those subject to control conditions. Respiration acclimated to seasonal shifts in temperature, more intensively through summer than winter and in throughfall-exclusion than control trees. Foliar concentration of soluble sugars was positively correlated with R15 across seasons. * 4As leaf respiration decreased with increasing water deficit, and the relationship between water status and respiration did not differ between trees that had been exposed to 7 years of enhanced drought when compared with controls, we suggest that drier conditions projected for the Mediterranean may attenuate the stimulation of leaf respiratory CO2 release by global warming in Q. ilex forests.
Keywords: abiotic factor; canopy depth; Carbon; drought acclimation; mediterranean habitat; nonstructural carbohydrates; thermal acclimation; throughfall exclusion

Is selective thinning an adequate practice for adapting Quercus ilex coppices to climate change? - Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M.; OURCIVAL, JEAN-MARC; Limousin, Jean-Marc; Joffre, Richard; Rambal, Serge (Annals of Forest Science, 2011)
& Introduction Future climatic scenarios demand an increasing involvement of management for forest preservation, but little is known on how forestry practices will benefit stands in facing variation of climatic components. & Objectives We investigated how selective thinning affected the response of an old Quercus ilex coppice to 6 years of throughfall reduction. Plots thinned from below (≈30% basal area removal) and unthinned plots were subject to either throughfall exclusion (TE; ≈33% throughfall reduction) or normal rainfall. Stem diameter growth, stem survival, and seed and sprout production were measured. & Results TE did not have a significant effect on stem growth but it reduced the production of viable acorns. Also, in the absence of thinning, TE accelerated the mortality of small stems and stimulated the emergence of new sprouts. Thinning reduced stem mortality, enhanced growth of residual stems, and caused a profuse emission of resprouts. Thinning also increased total seed production, but the crop had a large proportion of aborted seeds, especially in those areas subject to TE. & Conclusion The mere elimination of suppressed and diseased stems in abandoned Q. ilex coppice stands helps remaining trees to cope with current and future (probably longer and more intense) droughts. Potentially drier conditions might attenuate the success of thinning in producing a viable seed crop.
Keywords: Drought; forest adaptation strategy; seed production; sprouting; stem growth